Extinct birds, and those in danger of extinction - Steele, Philip, 1948- (New York : F. Watts, 1991)
Describes the physical characteristics and habits of prehistoric birds that are now extinct, such as archaeopteryx, and those of species that have either recently vanished or are facing extinction.
Includes index.
Appraisal-Science Books for Young People
5.2
3-6
3-6
Keywords: Birds, Fossil -- Juvenile literature; Extinct animals -- Juvenile literature; Birds, Fossil; Extinct animals; Birds, Fossil; Extinct animals